Alternatif Penyelesaian Waris Pengganti Di Indonesia - Ahmad Insya' Ansori; Moh. Ulumuddin (Sekolah Tinggi Agama Islam At-Tahdzib, Ngoro, Jombang, Indonesia, 2019)
The difference between salaf scholars and modern scholars about the successor to successors. Salaf scholars state that